Isolation of epidemic poliovirus from sewage during the 1992-3 type 3 outbreak in The Netherlands. - van der Avoort, H. G. (Cambridge University Press, 1995)
To examine the extent of wild poliovirus circulation during the 1992-3 epidemic in the Netherlands caused by poliovirus type 3, 269 samples from sewage pipelines at 120 locations were examined for the presence of poliovirus. The epidemic virus strain was found in 23 samples, all from locations inside the risk area which contained communities that refuse vaccination for religious reasons. By sewage investigation, the wildtype virus was shown to be present in the early phase of the epidemic at two locations, one week before patients were reported from that area. The wild type 3 poliovirus was also detected retrospectively in a river water sample collected for other reasons three weeks before notification of the first poliomyelitis case, at a site a few kilometres upstream the home village of this patient. Oral poliovirus vaccine (OPV) virus was found at 28 locations inside or at the border of the risk area. Trivalent OPV was offered to unvaccinated or incompletely-vaccinated persons living in this region as part of the measures to control the epidemic.